How Far Has Zakat Efficiency been Researched? - Mimma Maripatul Uula; Nun Maziyyah (Islamic Social Finance, 2022)
This study aims to determine research trends regarding zakat efficiency topic, assess research collaboration relationships, and identify future research directions. The 52 sample articles published between 2011-2022 on zakat efficiency analyzed by qualitative and quantitative approaches, namely Bibliometric and Systematic Literature Review (SLR) methods. This research uses VosViewers software. It is known that the four sub-themes that dominate research related to zakat efficiency are: Collection and distribution of zakat, Zakat efficiency, Zakat governance, and Zakat performance. This study implies that there is still little research on zakat efficiency theme. Malaysia is the country that has published the most articles about zakat efficiency topic.